Attitudes towards implementation of surveillance‐based parasite control on Kentucky Thoroughbred farms – Current strategies, awareness and willingness‐to‐pay. (18th December 2014) - Robert, M.; Hu, W.; Nielsen, M. K.; Stowe, C. J.
Summary Reasons for performing study Traditionally, equine parasite control has relied heavily on frequent routine anthelmintic treatments applied at regular intervals all year round. However, current recommendations aim to employ a more surveillance‐based approach and it remains unknown to what extent these recommendations are being implemented on US horse farms. Objectives To describe equine parasite control on Kentucky Thoroughbred farms and evaluate respondents' willingness to pay for various attributes of surveillance‐based parasite control strategies. Study design Questionnaire survey performed among the membership of the Kentucky Thoroughbred Farm Managers' Club. Methods The survey collected demographic data and information about current parasite control strategies. Further, respondents were asked to choose between hypothetical parasite control strategies described with a combination of different attributes: costs, time and effort needed, hypothetical disease‐risk levels and hypothetical risks of anthelmintic resistance. Data were analysed with multivariable logistic analysis. Results About 26% responded to the survey (n = 112). Most respondents were concerned about anthelmintic resistance and incorporated veterinary advice in defining their deworming programme. However, almost 70% were following a traditional rotational deworming programme with little or no faecal surveillance. Respondents were willing to pay a premium for a product for which there is no known anthelmintic resistance and provided the highest possible decrease in health risks. The number of young horses on the farm, utilisation of veterinarian advice in developing a deworming programme, expressed concern about drug resistance in parasites and having documented drug resistance on the farm all associated significantly with the type of parasite control programme used. Conclusions Traditional approaches for equine parasite control are still widely used in the Kentucky Thoroughbred industry. The data suggest that respondents were only willing to make these changes if they could be given assurance that the surveillance‐based approach would prevent anthelmintic resistance and decrease health risks significantly for the horses.